Development of a Specialized Lathe Chuck for Turning Operations of Cast Iron Rope Wheels - Miturska, Izabela; Rudawska, Anna; Cubonova, Nadezda; Naprstkova, Natasa (Manufacturing Technology Journal, 2020)
The use of lathe chucks in machine building companies is the result of a great deal of work and the develop-ment of technical thought. Due to the progress and the possibility of increasing efficiency and at the same time relieving people from work that requires a lot of effort, especially physical effort, the use of better and more efficient production methods is a target that should be pursued nowadays. In the manufacturing pro-cess, these objectives can be achieved with the use of dedicated equipment. The following work will present an example of a lathe chuck specialized in turning operations. The aim of the work was to use a universal chuck as a base for designing and manufacturing a specialized chuck so that it is possible to mount rope wheels with diameters from 240 to 580 mm. This would eliminate the necessity of time-consuming changeo-vers. In addition, it is assumed that the handle must meet the conditions imposed by the limited number of tools and the working dimensions of the machine. The machining process itself was also important, where the most advantageous solution was to perform most of the operations in one clamping.
Keywords: Specialized lathe chuck; Turning operations; Rope wheels